Pendampingan Program Pengembangan Ekowisata Mangrove dengan Kegiatan Konservasi Lingkungan - Khambali Khambali; Rachmaniyah Rachmaniyah; Fitri Rokhmalia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Ecotourism or Nature Tourism is a tourism activity that is responsible for unspoiled areas that are managed according to natural rules, with the aim of enjoying the beauty of nature which involves elements of education, understanding and support for efforts to conserve nature and increase income and welfare. The development of ecotourism in the form of sustainable tourism villages based on community empowerment is an effort to include the role of the community in tourism village activities known as "Community Based Development". The purpose of this program was to improve environmental health and insight in the field of environmental health and improve the quality of life of the community, especially the people of Wonorejo Village, Rungkut District, Surabaya City. Community service activities carried out in Mangrove Ecotourism were environmental conservation in the form of reforestation by planting trees and mangroves. Planting 3000 mangrove plants in the sea, providing plant seeds involving the Surabaya City Plantation and Park Service. Furthermore, it is recommended to conduct research on Pb levels, soil conditions and various types of plants to determine phytoremediation using plants. It is also necessary to periodically evaluate the function of mangroves that have been planted. Keywords: ecotourism; mangroves; environmental conservation ABSTRAK Ekowisata atau Wisata Alam adalah kegiatan pariwisata yang bertanggung jawab atas kawasan yang masih alami yang dikelola sesuai kaidah alam, dengan tujuan menikmati keindahan alam yang melibatkan unsur edukasi, pemahaman dan dukungan bagi upaya pelestarian alam serta peningkatan pendapatan dan kesejahteraan. Pengembangan ekowisata berupa desa wisata secara berkelanjutan berbasis pemberdayaan masyarakat merupakan upaya memasukkan peran masyarakat dalam kegiatan desa wisata yang dikenal dengan istilah “Community Based Development”. Tujuan dari program ini adalah untuk meningkatkan kesehatan lingkungan dan wawasan dalam bidang kesehatan lingkungan serta meningkatkan kualitas hidup masyarakat khususnya masyarakat Desa Wonorejo, Kecamatan Rungkut, Kota Surabaya. Kegiatan pengabdian masyarakat yang dilakukan dalam Ekowisata Mangrove yaitu pelestarian lingkungan berupa reboisasi dengan penanaman pohon dan mangrove. Penanaman 3000 tanaman mangrove di laut, pemberian bibit tanaman melibatkan Dinas Perkebunan dan Pertamanan Kota Surabaya. Selanjutnya direkomendasikan penelitian tentang uji kadar Pb, kondisi lahan dan berbagai jenis tumbuhan untuk menentukan fitoremediasi menggunakan tumbuhan. Diperlukan juga evaluasi secara berkala terhadap fungsi mangrove yang telah ditanam. Kata kunci: ekowisata; mangrove; konservasi lingkungan